The two faces of Graeco-Roman Egypt - Verhoogt, A. M. F. W.; Vleeming, S. P. (Papyrologica Lugduno-Batava;, 1998)
On May 1st, 1998 Professor P.W.Pestman retired from academic teaching. His contributions to the field of papyrology are well known: he has continually stressed the importance of Egyptian sources for the study of Greek and Roman Egypt, and the importance of studying the Greek and Egyptian documentation together, in context. Indeed, he has been among the first to link the formerly separate Greek and Egyptian documentation, establishing modern papyrological practice. He has thus given an Egyptian face to Graeco-Roman society, to complement the Greek face that had previously dominated papyrology. The present volume contains twelve contributions by members and alumni of the Papyrologisch Instituut that illustrate the two faces of Graeco-Roman Egypt and show how they may be tied together.